Vaccines against Shigella and enterotoxigenic Escherichia coli: A summary of the 2016 VASE Conference. Issue 49 (14th December 2017) - Walker, Richard I.; Wierzba, Thomas F.; Mani, Sachin; Bourgeois, A. Louis
Highlights: The inaugural vaccines against Shigella and ETEC Conference was held in June 2016. Shigella and ETEC pose a substantial public health burden in poor communities. A variety of promising vaccine approaches for Shigella and ETEC are being studied. Combined vaccines offer an attractive strategy for reducing disease burden. Abstract: PATH hosted the inaugural Vaccines Against Shigella and Enterotoxigenic Escherichia coli (VASE) Conference in Washington, DC in June 2016, bringing together experts from around the world for a highly collaborative forum to discuss progress in the development of new enteric vaccines. Diarrheal disease and long-term sequelae caused by infections with the bacterial pathogens Shigella and enterotoxigenic E. coli (ETEC) pose a significant public health burden in low-income communities. There are currently no licensed vaccines against these pathogens, and the global health community has recently prioritized their development. The 2016 VASE Conference aimed to accelerate communication and progress among those working in the enteric vaccine field to make Shigella and ETEC vaccines a reality as quickly as possible. Research presented in oral and poster presentations at the VASE Conference covered a range of topics, including: the global burden of disease and public health case for Shigella and ETEC vaccines; current vaccine candidates in development; immunology and host responses to the pathogens; and the rationale for and status of combined Shigella -ETEC vaccine candidates. This article reviews key points and highlighted research presented in each of the plenary conference sessions and poster presentations at the 2016 conference. Planning for the 2018 VASE Conference is underway and will likely provide an important platform for sharing the latest updates on Shigella and ETEC vaccine research efforts and maintaining the momentum for accelerating this work. It is also expected that the VASE Conference will continue to provide a unique opportunity for those in the enteric vaccine field to share ideas, make connections, and create workable plans to make Shigella and ETEC vaccines a reality. (Updates available at:www.vaseconference.org .)